A Comparative clinical study of Ksharsutra ligation and Lateral Internal Sphincterotomy in the management of Parikartika (Chronic Fissure-in-Ano) - Bhadja, Dr. Manoj (International Journal of Pharmaceutical & Biological Archive, 2018)
Background: Parikartika which resembles fissure-in-ano described as a complication of various diseases in Ayurvedic texts such as Vatika jwara, Vatika pakwa atisara, Sahaja arsha, Kaphaja arsha, Arsha purvarupa, Udavarta, complication of pregnancy (Garbhini), unlawful administration of purgative or enema (Basti), complication of Vamana and Virechana. As Ksharsutra , proven successful treatment modality for fistula-in-ano and piles to try its efficacy in chronic fissure-in-ano. Aim: To compare Apamarga Ksharsutra ligation and Lateral Internal Sphincterotomy (LIS) in the management of Parikartika (Chronic fissure-in-ano). Materials and Methods: Total 30 patients of Parikartika were selected and randomly divided in to two Groups (15 in each group). In group-A, Ksharsutra ligation with maximum possible anal dilatation was carried out while in group-B Lateral Internal Sphincterotomy with excision of skin tag was carried out under local anesthesia. Relief in symptoms and post operative complications in subjects were assessed for 4 weeks and follow up period was 1 month. Results: In both groups, significant results were found individually but difference was statistically insignificant. Duration required for relief in post- operative pain, bleeding, swelling and wound healing was found more in group-A (Ksharsutra) than group-B (LIS). Conclusion: Lateral Internal Sphincterotomy produced better results in compare to Ksharsutra ligation in the management of Parikartika (Chronic Fissure-in-Ano).